Socio-Economic Covid-19 Survey (SECS) - Kleinert, Manuel; Alm, Elisabeth; Christian, Nele; Lang, Jonas; Kammer, Bianca; Kunz, Marlene; Plank, Salome; Treibel, Maj; Schwarz, Maureen; Stierig, Lena; Justus Liebig University Giessen (My University, 2021)
Survey in four countries about the socio-economic impact of Covid-19 in July 2020.
Keywords: COVID-19; Corona Virus; Socio Economic Status; Inequality; Wealth; Income; Pandemic; ddc:300